Clinical leadership development in Australian healthcare: a systematic review. Issue 12 (22nd December 2020) - Pizzirani, Bengianni; O'Donnell, Renée; Skouteris, Helen; Crump, Bernard; Teede, Helena
Abstract: Despite clear priority and high costs of leadership capability programmes in healthcare, and significant investments into improving clinical leadership, there remains a prominent gap around evidence of effectiveness or impact on patient outcomes in Australia. We aimed to conduct a systematic review on postgraduate clinical leadership programmes to gather learnings on the processes, theoretical underpinnings, and impact of such programmes for medical and other health professionals. Our search included empirical, peer‐reviewed evaluations of Australian clinical leadership development programmes published between November 2008 and March 2019 and yielded 3284 records. Four studies met criteria. Findings revealed that currently, little value is placed on formal evaluations and peer‐reviewed publication including assessment of individual, organisational or system level impacts of clinical leadership development programmes, with limited evidence available on effective approaches to clinical leadership development in the Australian healthcare system.